ISOLASI, KARAKTERISASI BAKTERI ASAM LAKTAT, DAN ANALISIS PROKSIMAT DARI MAKANAN FERMENTASI BEKASAM IKAN MUJAIR (Oreochromis mossambicus Peters) - Olivia Nisa Mumtianah; Endang Kusdiyantini; Anto Budiharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Bekasam is one of the traditional fermented food made from freshwater fish with the addition of salt and carbohydrate sources. Mozambique fish is used as a raw material, because it has high protein content and can be easily obtained in the market at affordable prices. Mozambique fish is used to make bekasam with the addition of salt as much as 18% of the weight of the fish and brooded for 48 hours, then added with toasted rice as much as 15% of the weight of the fish and fermented for 7 days. This study aimed to isolate and characterize lactic acid bacteria and analyze the nutritional value of mozambique fish bekasam. The methods used were isolation, characterization and proximate analysis of the mozambique fish bekasam. Isolation of lactic acid bacteria was carried out on mozambique fish as a control, mozambique fish before and after the addition of toasted rice. Isolation obtained 6 isolates of Gram positive bacteria, 5 isolates of cocci shaped bacteria and 1 rod shaped bacteria. Based on morphological and physiological tests, six isolates were Gram positive, non motile, catalase negative, positive to produce acid and had proteolytic activity. Bekasam mozambique fish contained as much as 0.64% lactic acid and pH is 5.39. The results of the proximate analysis bekasam mozambique fish showed that the fermentation process increased the nutritional value bekasam quality mozambique fish with 5.5270% water content, 33.0628% ash content, 0.0788% crude fiber content, 45.0546% crude protein content, 7.9419% crude fat content and 13.9407% carbohydrate content. Keywords : bekasam , lactic acid bacteria , isolation, characterization, proximate analysis